Poklicna izgorelost pri šolskih svetovalnih delavcih v osnovni šoli - Kovač, Jernej; Javornik Krečič, Marija (Revija za elementarno izobraževanje, 2014)
Professional Burnout among School Counselors in Basic School. School counsellors are often stressed due to the nature of their work. This stress can, when unsatisfyingly treated, easily evolve to a professional burnout. In Slovenia no research with the specific aim to explore the professional burnout among school counsellors has been performed so far. Hence the aim of the present research is to compensate this shortage in the area of school counselling. The paper presents some theoretical foundations of occupational burnout and results of empirical research. The purpose of the empirical research was to determine the perceptions of occupational burnout among school counselors. We were interested in the level of occupational burnout and existing differences in terms of age, education and presence of supervision. We analysed the results of the present study according to three dimensions of occupational burnout in school counselors, namely lesser fulfilment, exhaustion and depersonalization. Results have shown that the perceived level of the avarage occupational burnout in most school counsellors is relatively homogenous. Within the individual dimensions of professional burnout among school counselors the sense of lesser fulfillment has proven to be the most strongly expressed. The study also showed that the greatest differences are seen in the dimension of lesser fulfilment and emotional exhaustion with regard to education and presence of supervision.